Design and Modelling of a Generator for Pico Hydropower System - Osman, Nur Sabrina (Universiti Teknologi PETRONAS, 2021)
Hydropower is one of the method to produce electrical power with the utilization of water power. Most of the time, hydropower plant sizes are huge due to the dam construction which often leads to the destruction of environment. Small scale hydropower system such as pico hydropower is a great alternative as it does not require a big dam for water storage. It usually utilizes the natural flow of water in river to rotate the turbine which will then turn the generator module that will convert mechanical energy to electrical energy. This hydropower system offers an affordable, efficient, clean, and reliable alternative of electricity generation and also often is less environmentally damaging than large-scale hydroelectric system. In Malaysia, there are still off-grid rural area that does not have supply to electricity due to their location being far from the city and deep in the forest. Hence, pico-hydropower system is a great alternative for the electrification of the rural areas while also being environmentally safe. This project focuses on the design and optimization of a generator with 100 W output for the proposed pico-hydropower system. The designs are simulated using the ANSYS software to obtain the performance of back-EMF, flux linkage and flux distribution. The design were then optimized by varying the pole per slot pair and by varying the magnet length. The results proved that the pole per slot pair and magnet length affects the performance of the generator in terms of induced back-EMF, output power and efficiency. The simulation results also show that it is possible to obtain 100 W output with the proposed and optimized generator design.